2018
DOI: 10.1002/uog.17523
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal prediction of postnatal large‐for‐dates neonates using a simplified MRI method: comparison with conventional 2D ultrasound estimates

Abstract: MRI planimetry using our purpose-designed semi-automated method is not time-consuming. The predictive performance of MRI-EFW performed immediately prior to or remote from delivery is significantly better than that of US-EFW for the prediction of large-for-dates neonates. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…There is some contradictory evidence for whether the precision of EFW can be improved by three-dimensional (3D) ultrasound volumetry [62][63][64] . Recent evidence suggests that EFW using magnetic resonance imaging (MRI) may be more accurate than ultrasound in the prediction of both SGA and LGA neonates 65,66 . Assessments of the value of 3D ultrasound and fetal MRI were beyond the scope of our study.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…There is some contradictory evidence for whether the precision of EFW can be improved by three-dimensional (3D) ultrasound volumetry [62][63][64] . Recent evidence suggests that EFW using magnetic resonance imaging (MRI) may be more accurate than ultrasound in the prediction of both SGA and LGA neonates 65,66 . Assessments of the value of 3D ultrasound and fetal MRI were beyond the scope of our study.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…A more accurate method of EFW could produce better outcomes by restricting interventions such as induction of labour and caesarean section to those fetuses at greatest risk of suspected macrosomia. Some publications have already demonstrated that MRI-derived EFW close to delivery is more accurate than US, with a precision superior to that of US using birth weight as a golden standard,14–23 and a recent meta-analysis has confirmed this promising accuracy 24…”
Section: Introductionmentioning
confidence: 97%
“…In a group of 270 patients who underwent MRI examinations 48 hours before elective birth, the fetal weight was evaluated retrospectively using the semiautomated technique and compared with actual birthweight. The detection rate of LGA (defined as greater than 95th centile for gestation) was 98% for a fixed false positive rate (FFPR) of 10% in comparison with 67% using 2D‐US estimates, while in the SGA group (defined as less than 10th centile for gestation), the rate of detection was 100%, or 18 out of 18 fetuses, for a FFPR of 10% (95% CI, 82‐100) compared with only 78% (95% CI, 52‐94) for 2D‐US …”
Section: Review Of Available Literaturementioning
confidence: 99%